Psychotherapy Relationships That Work 2019
DOI: 10.1093/med-psych/9780190843960.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style

Abstract: Attachment theory, developed by Bowlby to explain human bonding, has profound implications for conducting and adapting psychotherapy. We summarize the prevailing definitions and measures of attachment style. We review the results of three meta‐analyses examining the association between attachment anxiety, avoidance, and security and psychotherapy outcome. Fourteen studies were synthesized, which included 19 separate therapy cohorts with a combined sample size of 1,467. Attachment anxiety showed a d of −.46 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 0 publications
0
26
1
3
Order By: Relevance
“…() and Levy et al. (), who found insecure attachment to be negatively related with outcome, but contradicts with findings reported by Wiebe and Johnson (). We conjecture that these contradictory findings may be explained by a severity effect.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…() and Levy et al. (), who found insecure attachment to be negatively related with outcome, but contradicts with findings reported by Wiebe and Johnson (). We conjecture that these contradictory findings may be explained by a severity effect.…”
Section: Discussionmentioning
confidence: 78%
“…Research about associations between baseline insecure attachment or relational distress on the one hand, and treatment outcome on the other, is inconclusive. Insecure attachment was shown to have negative relations with outcome in a meta‐analysis on individual therapy (Levy, Ellison, Scott, & Bernecker, ) and a study on couples therapy (Conradi, De Jonge, Neeleman, Simons, & Sytema, ), while others found positive associations in couples therapy (c.f. Wiebe & Johnson, ).…”
mentioning
confidence: 99%
“…Meyer, Pilkonis, Proietti, Heape, and Egan (), following 149 psychiatric patients treated with psychotherapy and/or pharmacotherapy, found better treatment outcome for the patients initially classified as secure. A review of three meta‐analyses counting fourteen outcome studies ( n = 1,467) also reported better treatment outcome for patients with secure attachment, while a high anxious attachment predicted worse outcome in psychotherapy (Levy, Ellison, Scott, & Bernecker, ). Attachment style may be seen as moderating and mediating variables, and as a meaningful outcome in itself, in complement to symptom change (Daniel, ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to borderline pathology, all attachment studies using interview measures (George & West, , ; Main & Goldwyn, /1988/1996) and half of the attachment‐style studies reported a strong association between borderline personality disorder (BPD) and indices of disorganized attachment with unresolved trauma, often combined with preoccupied or fearful attachment strategies (Agrawal, Gunderson, Holmes, & Lyons‐Ruth, ; Bakermans‐Kranenburg & van IJzendoorn, ; Buchheim et al, ; Buchheim & George, ; Levy et al, ). Several studies have examined how attachment representations or styles may relate to the psychotherapy outcome (e.g., Levy, Ellison, Scott, & Bernecker, ; Taylor, Rietzschel, Danquah, & Berry, ). In various studies, successful psychodynamic psychotherapy was associated with a secure or organized attachment representation (Buchheim et al, , ; Levy et al, ) or style (Meyer, Pilkonis, Proietti, Heape, & Egan, ; Mosheim et al, ; Stefini et al, ; Strauss et al, ).…”
Section: Introductionmentioning
confidence: 99%